EPIDEMIOLOGY OF PROSTATE CANCER IN THE VORONEG REGION: SPATIO-TEMPORAL STATISTICS - O. E. Arhipova; E. A. Chernogubova; S. A. Kurolap; S. A. Yeprintsev (Вестник урологии)
The article presents the analysis of morbidity from prostate cancer with consideration of regional differences in the level of the health and environmental safety. Analysis was conducted of the level of incidence of prostate cancer in the Voronezh region for the period 2001 to 2015. The Model of conditionality of distribution of oncological diseases has provided a number of results, significantly expanding the scope and use of medical and environmental monitoring. The incidence of cancer of the prostate in the Voronezh region remained high for the past decade. The use of space-time statistics in conjunction with traditional statistical methods reveals the territorial medical and environmental contrast (group of regions with a different rating, the quality of public health), the territorial heterogeneity of incidence of prostate cancer, and the presence of "hot spots" of disease. The results can serve as a basis for the directional analysis of factors causing increase risk of cancer and development on these basis strategies for monitoring and prevention of cancer diseases in the Voronezh region.